A protein- and fiber-rich diet with astaxanthin alleviates high-fat diet-induced obesity in beagles - Xue, Jinhua; Lu, Yuanyuan; Zou, Toujun; Shi, Wei; Wang, Shuang; Cheng, Xu; Wan, Juan; Chen, Yun; Wang, Min; Wang, Qingzheng; Yang, Xia; Ding, Mingxing; et al. (Frontiers in Nutrition, 2022)
Background and aims Overweight or obesity is one of the most prevalent health burdens in companion pets and predisposes subjects to multiple comorbidities and reduced longevity. Dietary management and sufficient exercise are effective options for weight loss but challenged by modern lifestyle and calorie control-triggered malnutrition. Therefore, this study aimed to develop a formulated obesity control diet characterized by protein- and fiber-rich diet and supplemented with astaxanthin. We systemically evaluated global influences of the designed weight-loss diet on metabolic homeostasis in an obese beagle model. Materials and methods Beagles were induced for obesity by a 24-week HFD treatment and then included into weight-loss programs. Briefly, obese beagles were randomly assigned to two groups that were fed with a formulated weight-loss diet or control diet, respectively. Body weight and body condition scoring (BCS) were analyzed biweekly. Computed tomography (CT), nuclear magnetic resonance imaging (MRI) measurements, and blood and adipose tissue biopsies were collected at 0 and 8 weeks. Plasma lipids and adipocyte size were also measured after 8 weeks of weight-loss diet feeding. The global influence of the formulated diet on the whole spectrum of gene panels were examined by adipose RNA assays. Results Twenty-four weeks of continuous HFD feeding significantly induced obesity in beagles, as evidenced by increased body weight, BCS, abdominal fat mass, and serum lipid levels. The obese and metabolic condition of the modeled canine were effectively improved by an 8-week weight-loss diet administration. Importantly, we did not observe any side effects during the weight loss duration. Transcriptional analysis of adipose tissues further supported that a weight-loss diet significantly increased energy metabolism-related pathways and decreased lipid synthesis-related pathways. Conclusion The prescribed weight-loss diet exhibited profound benefits in canine weight management with well safety and palatability. These findings support effective strategies of nutritional management and supplementation approaches for weight control in companion animals.